2016
DOI: 10.1016/j.wjorl.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Deep neck space infection – A retrospective study of 270 cases at tertiary care center

Abstract: ObjectiveTo review the clinical findings in deep neck infections and identification predisposing factors of these complications.MethodsIn this study, 270 patients with deep neck infections were studied retrospectively, study conducted in the Department of Ear, Nose and Throat, Dr. Shankarrao Chavan Government Medical College, Nanded, Maharashtra, India, from March 2013 to March 2016.ResultsAnalysis showed that males are most likely to have deep neck space infections (DNSI). Odontogenic and tonsillar causes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 29 publications
4
45
2
1
Order By: Relevance
“…A study by Bottin et al showed similar results to ours where the majority of their patients complained of neck pain (71.1%), followed by odynophagia (54.2%) and dysphagia (51.8%) [7]. Pain was also the most commonly reported symptom in Gujrathi et al, accounting for 81.48%, followed by swelling 77.78% [3].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…A study by Bottin et al showed similar results to ours where the majority of their patients complained of neck pain (71.1%), followed by odynophagia (54.2%) and dysphagia (51.8%) [7]. Pain was also the most commonly reported symptom in Gujrathi et al, accounting for 81.48%, followed by swelling 77.78% [3].…”
Section: Discussionsupporting
confidence: 83%
“…Although DNSI can affect people of all ages, in our research, people aged 41-60 years were the most affected while persons above 70 years were the least affected. A study by Gujrathi et al found that the majority of their patients were in the third decade (21.85%) followed by the fourth decade of life (18.15%) [3]. Results by Har-El et al also showed that almost 50% of their patients were in their thirties or forties [4].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Temporal space abscess is rare and has been rarely reported in the literature with an incidence of 0.74%. 1 Peterson stated that temporal space is divided into superficial and deep temporal spaces. The superficial temporal space extends superiorly to the pericranium, lateral to the temporalis muscle and medial to the temporoparietal fascia, inferiorly it is continuous with the masseteric space.…”
Section: Discussionmentioning
confidence: 99%
“…Most common deep neck space infection remains Ludwig's angina followed by peritonsillar, submandibular, and parotid abscess. 1 Temporal and infratemporal space infections are rare. The main etiological factors are maxillary sinusitis, tonsillitis, maxillary sinus fracture, temporomandibular arthroscopy, drug infection, dental caries and extraction of infected and non-infected tooth.…”
Section: Introductionmentioning
confidence: 99%